Multi-Mode Transmitter Based on Silicon Microring Modulators - Mengyuan Ye; Yunlong Li; Weilun Zhang; Li Liu; Yang Shi; Yu Yu (IEEE Photonics Journal, 2022)
We propose and demonstrate a multi-mode transmitter based on cascaded silicon microring modulators (MRMs). By sharing bus waveguide at drop ports of the MRMs, data modulation and mode multiplexing could be achieved simultaneously, resulting in a simplified layout with compact size. For the proof-of-concept demonstration, multi-mode transmitter for TE0 and TE1 modes is fabricated. Transmission of non-return-to-zero on-off keying (NRZ-OOK) signals with the bit rate of 2 × 25 Gbps is experimentally demonstrated. Measured eye diagrams and bit error rate (BER) results indicate good transmission performance.